Phenomenology Study: Community Perception Of Lush Disease In The Working Area Of Puskesmas Talango, 2020 - Hidayat, Mukhlish; Irawati, Diana; Waluyo, Agung (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Leprosy (Morbus Hansen) is a chronic infectious disease of the skin caused by Mycobacterium leprae, leprosy is also known as "the great imitator disease" because of the similar manifestations to other skin diseases such as fungal infections so that a person rarely realizes that he has had leprosy. This qualitative study was conducted to explore community perceptions about leprosy with 6 male and 4 female participants. The method used is a phenomenological approach with consecutive sampling as a sampling technique. There are 5 themes obtained in this study, namely factors that influence perception, the form of public perception of leprosy patients, community behavior in preventing leprosy transmission, hope for leprosy patients, and hope for health workers. Health education about leprosy is needed by the community to deepen their knowledge about leprosy and the attitude of the community towards people with leprosy.